Faster chemistry at surfaces - Walker, Robert A. (Nature chemistry, 2021)
The physical properties of a liquid at an interface differ from bulk solution limits, but how this affects chemical reactivity is unclear. Now, ultrafast, surface-sensitive vibrational spectroscopy has revealed that the light-induced reaction of phenol with water is four orders of magnitude faster at the water surface than in bulk.